Description of a new species of the genus Ptychozoon (Squamata: Gekkonidae), representing a new national record of this genus from southern Yunnan Province, China - Wang, Ying-Yong; Wang, Jian; Liu, Zu-Yao (Zootaxa, 2016)
A new species of the Parachute Gecko, Ptychozoon bannaense sp. nov., is described on the basis of two specimens from Xishuangbanna, Yunnan Province, China. The new species can be distinguished from eight known congeners by the following combination of morphological characters: body size moderate, SVL 83.2–87.5 mm; rostral with a short dorsomedian groove; dorsal head and body covered with granular scales without enlarged tubercles, but male with several enlarged tubercles on the occipital region; two supranasals separated from each other by a large internasal; the absence of a predigital notch in the preantebrachial cutaneous flap; male possesses 17 preanofemoral pores in a continuous scale row; tail tubercle absent, 24 pairs of lateral denticulate cutaneous lobes of the tail; width of tail and caudal lobes progressively decreasing posteriorly; the terminal caudal flap short, semicircle, not expanded; lack of lobe fusion at the terminal caudal flap border; the presence of four dark dorsal bands between fore- and hind limbs insertions, the third and fourth dorsal bands fused into a X-shaped mark. The new species is also divergent from known taxa in mitochondrial gene sequences, supporting its recognition based on morphological characters. The discovery and description of Ptychozoon bannaense brings the total number of Ptychozoon to nine, and represents the first record of the genus Ptychozoon in China.